PENGARUH PENAMBAHAN KADAR AIR TERHADAP KUAT GESER TANAH PADA LOKASI LONGSOR KOORDINAT 2°08'01"N 98°34'06"E JALAN PROVINSI DOLOKSANGGUL-PAKKAT - Semangat Marudut Tua Debataraja; Jupiter Bremalemta Sembiring; Yusuf Aulia Lubis; Rahidun Simangunsong (Jurnal Sains dan Teknologi ISTP, 2023)
The shear strength of the soil is the resistance force exerted by the soil grains against the push or pull. This study aims to determine the physical and mechanical properties of the soil, to determine the effect of adding and reducing water content on the shear strength of the soil against the direct shear test and the free compressive strength test in Arbaan Village, Kec. Onan Ganjang, Humbang Hasundutan District. This study uses testing methods in the laboratory. The results of testing the physical properties of the original soil according to USCS are classified as CL group, namely inorganic clay soils with low to medium plasticity, gravelly clay, sandy clay, silty clay, lean clays, according to AASHTO these soils fall into group A-6. Silt – Clay (Silt Clay). The results of testing the mechanical properties of the original soil obtained values, (c) = 0.141kg/cm2, water content 33.15% and (qu) = 1.282 kg/cm2 and (ϕ) = 12˚ from these parameters the value was obtained (τ) = 0.207 kg/cm2 Clay with the addition of water 12.5%, 15% and 17.5%, an increase in the value of water content 20.62%, 24.75% and 28.87%, air dry clay 4 hours, 6 hours and 8 hours there was a decrease in the value of the water content of 3.56%, 5.58% and 8.93%, changes in the value of the water content in the soil affected the values ​​of shear strength, cohesion and compressive strength values. During the drying process it greatly influences the soil mechanical properties test and increases the shear strength and compressive strength values ​​of the original soil.